Short communication: Mycosporine-like amino acids protect natamycin against photodegradation in milk exposed to fluorescent or light-emitting diode light - Teixeira, G. H.A. [UNESP]; O'Keefe, S. F. (American Dairy Science Association, 2019)
Natamycin has been used as a natural antimicrobial in dairy products, but the poor light stability of natamycin can limit usefulness in food products. Mycosporine-like amino acids are strong UV absorbers and might be useful as an additive to decrease light-induced degradations. Therefore, the objective of this study was to evaluate the photoprotective effect of mycosporine-like amino acids (MAA) in cow milk stored under 2 lighting conditions in retail commercial display cabinets with fluorescent and high intensity light-emitting diode illumination. When milk was exposed to both fluorescent and light-emitting diode light, natamycin degradation was very fast, and only 17.1 ± 0.9% of its original concentration was observed after 8 d at 4.0°C. On the other hand, by adding MAA into milk, natamycin was retained at 82.2 ± 0.9% and 92.2 ± 0.9% when low and high MAA levels were used, respectively. However, high MAA levels resulted in color changes. Therefore, MAA at low levels had a photoprotective effect for natamycin stability in cow milk exposed to light in refrigerated glass containers.
Keywords: milk; mycosporine-like amino acid; natamycin